HOW IS THE PERFORMANCE APPRAISAL SYSTEM FOR SMALL AND MEDIUM ENTERPRISES IN THE LIVESTOCK INDUSTRY? EXPERIMENTAL STUDY IN INDONESIA - Ferdi Fathurohman; Rita Purwasih; Nurul Mukminah; Fitri Suciati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
The performance evaluation techniques have been important tools of competitive strategy to enhance organizational productivity and profitability. This study aims to find the factors that promote the deployment of performance evaluation techniques in livestock industry SMEs in Indonesia. In this study we examine the relation between three institutional factors (Imitation, Coercion and Normality), four contigency factors (Strength of competitive market, Participation of business owners, Advanced technology and The qualifications of accountants) and the deployment of performance evaluation techniques in livestock industry SMEs in Indonesia. The study applies a quantitative research methodology and uses a questionnaire method to collect the data. The study sample consists of 129 respondents. This study analyzes the data using the (SPSS) program. The results reveal a statistically significant relationship between the Strength of competitive market, Participation of business owners and Imitation and the deployment of performance evaluation techniques in livestock industry SMEs in Indonesia.